Compliance at night with low flow oxygen therapy: a comparison of nasal cannulae and Venturi face masks. Issue 4 (April 1995) - Costello, R W; Liston, R; McNicholas, W T
Abstract : BACKGROUND–The factors that influence nocturnal compliance among patients prescribed low flow oxygen therapy were determined and tolerance of nasal cannulae and Venturi face masks compared. METHODS–Two studies were performed: (1) a prospective study of 99 hospitalised patients prescribed low flow oxygen therapy, 49 on nasal cannulae and 50 on Venturi face mask; and (2) a prospective study of 20 separate patients with an acute respiratory disorder requiring low flow oxygen therapy who were given nasal cannulae and Venturi face mask on successive nights in random order. RESULTS–In study 1, 49 patients dislodged their device at least once during the night. Those using Venturi face masks and those over 75 years of age had the most dislodgements. In study 2 patients also dislodged Venturi face masks more frequently (mean (SD) 2.0 (2.4)) than nasal cannulae (0.7 (1.4)). Most patients expressed a preference for nasal cannulae. CONCLUSIONS–Nocturnal tolerance of nasal cannulae is superior to Venturi face masks, and this factor should be considered when choosing the method of oxygen delivery.